Calculus 10th Edition

Published by Brooks Cole
ISBN 10: 1-28505-709-0
ISBN 13: 978-1-28505-709-5

Chapter 2 - Differentiation - 2.4 Exercises: 88



Work Step by Step

$f(x)=8(x-2)^{-2}.$ $f'(x)=(8)(-2)(1)(x-2)^{-2-1}=-\dfrac{16}{(x-2)^3}=-16(x-2)^{-3}.$ $f''(x)=(-16)(-3)(1)(x-2)^{-3-1}=\dfrac{48}{(x-2)^4}.$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.